2022
DOI: 10.1101/2022.09.16.508239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse transcriptomic response of cellular system following low-dose exposure of mesoporous nanoparticles

Abstract: Mesoporous nanoparticles are an interesting drug delivery system that has generated considerable attention in the biomedical sector. Despite recent attempts to conduct safety assessments using traditional methods based on phenotypic data, our understanding of the underlying molecular processes produced by mesoporous NPs is still in its infancy. In the present study, RNA sequencing was used to assess the biological perturbations and the pathways induced in response to early exposure of two different mesoporous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Recently, Mittal D. revealed that exposure to MSN, ZnO and mesoporous carbon nanoparticles (MCN) resulted in the upregulation of over 200 ubiquitination pathway genes and the downregulation of over 100 transcripts. 48,49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mittal D. revealed that exposure to MSN, ZnO and mesoporous carbon nanoparticles (MCN) resulted in the upregulation of over 200 ubiquitination pathway genes and the downregulation of over 100 transcripts. 48,49…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Mittal D. revealed that exposure to MSN, ZnO and mesoporous carbon nanoparticles (MCN) resulted in the upregulation of over 200 ubiquitination pathway genes and the downregulation of over 100 transcripts. 48,49 We obtained information to classify the interaction based on the topological classification. We created the collective mapping of proteins using PPI interaction.…”
Section: Environmental Science: Nano Papermentioning
confidence: 99%
“…Additionally our another study was based on the transcriptomic analysis for the effect of MCN (Mesoporous carbon nanoparticles) and MSN in liver hepatoma cells that describes the regulation of common molecular pathways during initial interaction with the cellular system. These NPs perturbed pathways including DNA damage, repair, cell cycle regulation, transcription and ubiquitination are common among both MCN and MSN (Mittal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%